COMPARATIVE STUDY OF THE DRYING EFFECT OF SMOKING KILN ON FRESH FISH AND FROZEN FISH - Afolabi, B.O.; Adegboye, O. (International Journal of Research -GRANTHAALAYAH, 2019)
A gas powered fish smoking Kiln of 0.873 m3 capacity was utilized to investigate the possible variations in the heat utilized, body mass reduction and volume of gas utilized for drying fresh and frozen fish. Four fish types; two of frozen fish (mackerel and horse mackerel) and two of fresh fish (tilapia and catfish) of 2 kg each were prepared and were smoked for the period of 240 minutes with 30 minutes interval to measure mass reduction, volume of gas utilized, temperature variation in the smoking chamber and the vent. During the experiment, the maximum heat supplied was 128 OC and maximum heat utilized was 25 OC. The total volume of gas utilized is 5.2cm3 for the period of 240 minutes when the fishes were totally dried. The maximum body mass reduction was 1.3 kg and minimum was found to be 1.35 kg which corresponded to tilapia and horse mackerel, and mackerel respectively. The volume of gas utilized for drying each type of the fishes were ranged from 0.68 to 0.71 m3. Generally, the information gathered from this study establish the fact that other factors might be responsible for drying rate across the fresh fish and frozen fish.